THE EFFECT OF SUSTAINABILITY REPORT DISCLOSURE, GREEN ACCOUNTING AND CAPITAL INTENSITY ON THE COMPANY'S FINANCIAL PERFORMANCE: Empirical Study on Manufacturing Companies Listed on The Indonesia Stock Exchange in 2020-2024 - Siti Nurfadlilah; Yuli Novitasari; Miri Ardiansyah (International Journal of Economy, Education and Entrepreneurship (IJE3), 2026)
In the era of increasing globalization, companies are no longer judged solely on their financial performance, but also on the social and environmental impact they generate. Therefore, the disclosure of sustainability reports, the implementation of green accounting, and capital intensity are important factors in evaluating the company's performance. This study aims to analyze the influence of sustainability report disclosure, which consists of economic, social, and environmental dimensions, as well as green accounting and capital intensity, on the company's financial performance as measured by Return on Assets (ROA). This study uses a quantitative method using secondary data obtained from the annual reports and sustainability reports of manufacturing companies listed on the Indonesia Stock Exchange for the period 2020–2024. The sampling technique used was purposive sampling, while the data was analyzed using multiple linear regression analysis with the help of SPSS statistical software. The results show that the social dimension of sustainability reports, environmental dimensions of sustainability reports, and capital intensity have a significant influence on the company's financial performance, while the economic dimension of sustainability reports and green accounting do not have a significant effect on financial performance. However, at the same time, all variables have a significant effect on the company's financial performance. These findings show that a company's financial performance is not influenced by a single factor, but by a combination of various aspects of sustainability and overall management of the company's resources